Association of cognitive-emotional regulation strategies to depressive symptoms in type 2 diabetes patients - Mocan Andreia Ş; Iancu Silvia Ş; Băban Adriana S. (Sciendo, 2018)
Aim. The present cross-sectional observational study aimed to investigate the relation between cognitive-emotional regulation strategies and depressive symptoms in type 2 diabetes patients in the context of sociodemographic and clinical factors, of diabetes distress, perception of illness consequences and previous depression.